ANALYSIS OF FACTORS INFLUENCING LIQUIDATION VALUE OF AUCTION GUARANTEES (CASE STUDY AT PT BANK NEGARA INDONESIA (PERSERO), TBK. REMEDIAL AND RECOVERY IN PALEMBANG REGION) - Mitra Setiawan AP; Fachruddin Fachruddin; Nazaruddin Nazaruddin (Bajang Institute, 2023)
The purpose of this research is to analyze of factors influencing liquidation value of auction guarantees, case Study at PT Bank Negara Indonesia (Persero), Tbk. Remedial and Recovery in Palembang Region. This type of research is a quantitative descriptive research. The sample for this research is 35 collateral units that sell well during the 2019 to 2021 period at PT Bank Negara Indonesia (Persero), Tbk. Remedial and Recovery in Palembang Region. The analytical method uses multiple linear regression analysis. The results show that exposure time has a negative and significant effect on property market value at PT Bank Negara Indonesia (Persero), Tbk. Remedial and Recovery in Palembang Region. Economic growth has a positive and significant effect on property market value at PT Bank Negara Indonesia (Persero), Tbk. Remedial and Recovery in Palembang Region. Location has a positive and significant effect on property market value at PT Bank Negara Indonesia (Persero), Tbk. Remedial and Recovery in Palembang Region. Exposure time has a negative and significant effect on liquidation value of auction guarantees at PT Bank Negara Indonesia (Persero), Tbk. Remedial and Recovery in Palembang Region. Economic growth has a positive and significant effect on liquidation value of auction guarantees at PT Bank Negara Indonesia (Persero), Tbk. Remedial and Recovery in Palembang Region. Location has a positive and significant effect on liquidation value of auction guarantees at PT Bank Negara Indonesia (Persero), Tbk. Remedial and Recovery in Palembang Region. Property market value has a positive and significant effect on liquidation value of auction guarantees at PT Bank Negara Indonesia (Persero), Tbk. Remedial and Recovery in Palembang Region.